The Origin and Cultural Evolution of East Asian Cognitive Style: A Case Study of the Book of Changes (Yijing易經) - Nichols, Ryan (Journal of cognition and culture, 2021)
Experimental tests about cross-cultural differentiation of cognitive style conclude that East Asian and Western cognition differ. Tendencies described as East Asian include holism, non-linearity, expectation of change, relationalism, field dependence, causal pluralism, dialecticism, and a tolerance of contradiction. Cross-cultural psychologists generally refrain from discussing the intellectual history or cultural evolution of these differences, preferring to explain results on cognitive scales in terms of results on social scales assessed using present-day participants. The present article attempts to partially close this explanatory gap through detailed discussion of tendencies of East Asian cognitive style as represented in what is probably the most influential book in the history of East Asia, The Book of Changes. This study purports to show (a) that the content of the Yijing 易經 and its commentaries is best described in terms of the cognitive tendencies just mentioned, (b) that reading the Yijing activated those cognitive tendencies, and (c) that the Yijing attained prodigious influence on subsequent Chinese and East Asian cultures through four known mechanisms of cultural transmission. Informed by this case study, researchers of cross-cultural cognition may be positioned to develop a richer appreciation of the cultural representation and evolution of East Asian cognitive style in historical context.